2011
DOI: 10.1055/s-0031-1296905
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pharmacokinetic Data of Hypericin, Pseudohypericin, Hyperforin and the Flavonoids Quercetin and Isorhamnetin Revealed from Single and Multiple Oral Dose Studies with a Hypericum Extract Containing Tablet in Healthy Male Volunteers

Abstract: Hypericins, hyperforin and flavonoids are discussed as the main components contributing to the antidepressant action of St. John's wort (Hypericum perforatum). Therefore, the objective of the two open phase I clinical trials was to obtain pharmacokinetic data of these constituents from a hypericum extract containing tablet: hypericin, pseudohypericin, hyperforin, the flavonoid aglycone quercetin, and its methylated form isorhamnetin. Each trial included 18 healthy male volunteers who received the test preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 14 publications
4
23
0
5
Order By: Relevance
“…otic treatment, the anxiolytic effect of kaempferol and quercetin disappeared, whereas it was still present for the positive control diazepam [34]. Results support the hypothesis that the flavonoids are not only absorbed as aglyca, as is known from pharmacokinetic studies [35,36], but also as their hydroxyphenylacetic acid metabolites, and act therefore also as prodrugs.…”
Section: Dedicationsupporting
confidence: 73%
“…otic treatment, the anxiolytic effect of kaempferol and quercetin disappeared, whereas it was still present for the positive control diazepam [34]. Results support the hypothesis that the flavonoids are not only absorbed as aglyca, as is known from pharmacokinetic studies [35,36], but also as their hydroxyphenylacetic acid metabolites, and act therefore also as prodrugs.…”
Section: Dedicationsupporting
confidence: 73%
“…A number of studies have been reported on the pharmacokinetic profiles of the major active components in St. John's wort [95][96][97][98][99][100][101]. Staffeldt et al [99] first reported the pharmacokinetics of hypericin and psesdohypericin in 12 healthy subjects after oral administration of the St John's wort extract, LI 160 at single dose of 300, 900 and 1,800 mg. the maximum levels were 1.5, 4.1 and 14.2 ng/ml for hypericin and 2.7, 11.7 and 30.6 ng/ml for pseudohypericin, respectively, for the three dosages.…”
Section: St John's Wort (Hypericum Perforatum)mentioning
confidence: 99%
“…The second scan took place 2-4 hours after the last dose (t max for moclobemide was about 2 h, 26 and t max for compounds of St. John's wort formulation was 2-4 h 27,28 ).…”
Section: Treatment Protocolmentioning
confidence: 99%